Biased signaling of Ca2+-sensing receptors in cardiac myocytes regulates GIRK channel activity. (May 2019) - Kienitz, Marie-Cecile; Niemeyer, Anne; König, Gabriele M.; Kostenis, Evi; Pott, Lutz; Rinne, Andreas
Abstract: Ca 2+ -sensing receptors (CaSRs) belong to the class C of G protein-coupled receptors and are activated by extracellular Ca 2+ . CaSRs display biased G protein signaling by coupling to different classes of heterotrimeric G proteins depending on agonist and cell type. In this study we used fluorescent biosensors to directly analyze G protein coupling to CaSRs and downstream signaling in living cells. In HEK 293 cells, CaSRs displayed biased signaling: elevation of extracellular Ca 2+ or application of the alternative agonist spermine caused activation of Gi - and Gq -proteins. Adult cardiac myocytes express endogenous CaSRs, which have been implicated in regulating Ca 2+ signaling and contractility. Biased signaling of CaSRs has not been investigated in these cells. To evaluate efficiencies of Gi - and Gq -signaling via CaSRs in rat atrial myocytes, we measured G protein-activated K + (GIRK) channels. Activation of GIRK requires binding of Gβγ subunits released from Gi proteins, whereas Gq -signaling results in inhibition of GIRK channel activity. Stimulation of CaSRs by Ca 2+ or spermine failed to directly activate Gi and GIRK channels. When GIRK channels were pre-activated via endogenous M2 receptors, stimulation of CaSRs caused pronounced inhibition of GIRK currents. This effect was specific to CaSR activation: GIRK current inhibition was sensitive to NPS-2143, a negative allosteric modulator of CaSRs, and abrogated by FR900359, a direct inhibitor of Gq . GIRK current inhibition was also sensitive to the PKC inhibitor chelerythrine, suggesting that following activation of CaSR and Gq, GIRK currents are modulated by PKC phosphorylation. We conclude from this data that cardiac CaSRs do not activate Gi and affect GIRK currents preferentially via the Gq /PKC pathway.